Evaluation of the Effects of Different Solvents Extracts of Tribulus Terrestris Obtained Via Ultrasonic Extraction on Human Asthenozoosperm Activation In Vitro - Hikmat Fakhri Wassef (Journal of Global Pharma Technology, 2016)
Objective: This study was designed to evaluate the activity of different fractions of Tribulus terrestris Tt obtained via 20KHZ ultrasonic technique for different periods of extraction time and different solvents on different asthenozoospermic parameters in vitro. Material and method: The study was conducted on seventy-five asthenozoosperic patients. The sperm samples were activated in vitro (after liquefaction) with different doses of the extracts by using a direct simple layer method (DSLM) technique. Grades of sperm movement and sperm morphology were the main parameters tested. Results: Aqueous extract for 15 min. at a dose 0.02% showed the highest activity. Less activity was obtained by exposure of the sperm samples to a dose 0.002% aqueous acetonitrile (AA) extract for 15 min., 0.0002% dose of Ethanol (EtOH) and Methanol (MeOH) extracts for 15 min., 0.002% dose of (AA) extract for 15 min. and 0.002% dose of (EtOH) and (MeOH) extracts for 60 min. Exposure of asthenozoospermic samples to a dose of 0.0002% of (AA) extract for 60 min. gave the lowest activity. Conclusion: These finding indicated that the use of ultrasonically assisted extraction can obviously improve the activity of Tt extracts on asthenozoospermic patient’s parameters including the grades of sperm motility and sperm morphology.Keywords: Asthenozoospermia; Ethanol (EtOH); In vitro activation; Methanol (MeOH); Tribulus terrestris Tt; ultrasound extraction.